Controlling hybrid nonlinearities in transparent conducting oxides via two-colour excitation - M. Clerici (Nature Portfolio, 2017)
Metamaterials have enabled the tailored engineering of optical properties. Here, Clericiet al. show that independent interband and intraband nonlinearities in transparent conducting oxides allow dynamic optical control of the real and imaginary parts of the refractive index.